Afghanistan Post US Withdrawal: Security Challenges and Future Prospects - Muhammad, Imraz (Journal of Peace, Development and Communication, 2021)
After 9/11, the mission “Operation Enduring Freedom” was to root out terrorists from Afghanistan and to establish good governance in shape of representative democracy. However, the current internal political and law and order situation is worse even after years of US forces staying in Afghanistan. While President Trump has directed Pentagon to decrease nearly half of the more than 14,000 troops stationed in Afghanistan, Taliban are still powerful and have control over the large part of Afghanistan. All the regional and global powers have their interests in Afghanistan, have no clear policies for peace and development there, but everyone is in struggle to solve the Afghan problem according to their own interests install a government suited to their interest. To establish democracy, improve governance, rule of law and security situation in Afghanistan, the US withdrawal without proper homework will create more problems and lead to chaos. It is believed that the abrupt withdrawal may further strengthen the Taliban and increase violence in Afghanistan. This paper aims to investigate those internal and external factors which may become the cause of insecurity for Afghanistan. Furthermore, the research work enlightens over the solution of security problems in Afghanistan and suggests possible option. Key words: US withdrawal, Afghanistan, Regional Actors, Security issues, Challenges